Effect of Leadership Style, Motivation, and Job Satisfaction on Employee Performance of PT Dunkindo Lestari Medan - Neng Laela Dewi; Ina Namora Putri Siregar; Fitria Bidaya; Eva Christina Febriyanti Sianipar; Idris Edison Pardede (Journal of Research in Business, Economics, and Education, 2022)
Several elements, including as leadership approach, inspiration, and work contentment, must be addressed in order to increase employee output. A corporation's leadership approach is significant since a proper leadership approach has an effect on staff, that can increase the company's revenue. Conversely, if inspiration and work contentment are treated properly, they can boost productivity and enable staff feel at ease in the workplace. PT Dunkindo Lestari is the subject of this study as a result of a decline in the company's organizational effectiveness. This study employs a quantitative method and is descriptive explanation in nature, multi-linear regression, hypothesis testing, classical assumption tests, coefficient of determination, as well as reliability and Validity test are among the data analysis techniques employed. The census sampling technique was used in this study, something that obtained overall representative of the entire population. Information was gathered from 46 personnel who participated as respondents via questionnaires, interviews, and documentation assessments. Our findings revealed how leadership approach, motivation, and work contentment really have a favorable and noteworthy impact on staff output. With such a coefficient of determination of 42.5 percent, a value of F arithmetic > F table of (12.105 > 3.22), and a value of T arithmetic > T table for the variables leadership style (1.707 < 2.015), motivation (-1.368 < 2.015), and work satisfaction (3.837 > 2.015).